Americas : social dialogue and current processes of economic and technological changes - Morgado, Emilio (ILO LimaPE, 2002)
Addresses the special role of social dialogue in the Americas as a means of adjustment to the processes of globalization, economic and technological change. Studies social dialogue within the public sector. Discusses the centrality of dialogue, both as part of and point of reference for public policies, along with its functionality and suitability. Addresses the institutionalization of dialogue and the role of the Ministries of Labour vis-á-vis social dialogue.